2020
DOI: 10.1097/mpg.0000000000002631
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Pharmacodynamics, and Immunogenicity of Infliximab in Pediatric Inflammatory Bowel Disease

Abstract: Objectives: Infliximab (IFX), a monoclonal antibody directed against tumor necrosis factor alpha is a potent treatment option for inflammatory bowel disease (IBD). Dosing regimens in children are extrapolated from adult data using a fixed, weight-based dose, which is often not adequate. While clinical trials have focused on safety and efficacy, there is limited data on pharmacokinetic characteristics and immunogenicity of IFX in children. The objective was to provide a systematic overview of current literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 86 publications
0
28
0
2
Order By: Relevance
“…However, half of the patients required an increased dose or a shortened dosing interval to maintain a clinical response 29 . While the dose adjustments in the REACH trial were based on clinical evaluation and response, a target trough concentration of 3 to 5 μg/mL was soon identified for therapeutic drug monitoring in practice 30–32 . Revisiting the original analyses by Fasanmade et al revealed that 60% of children would achieve subtherapeutic trough concentrations with the labeled dose 33 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, half of the patients required an increased dose or a shortened dosing interval to maintain a clinical response 29 . While the dose adjustments in the REACH trial were based on clinical evaluation and response, a target trough concentration of 3 to 5 μg/mL was soon identified for therapeutic drug monitoring in practice 30–32 . Revisiting the original analyses by Fasanmade et al revealed that 60% of children would achieve subtherapeutic trough concentrations with the labeled dose 33 .…”
mentioning
confidence: 99%
“…The European Society for Paediatric Gastroenterology Hepatology and Nutrition subsequently revised their recommendations and advocates for up‐front intensification of the induction regimen for children <10 years of age 31 . Results of a systematic review further suggest that dose increases are necessary for all pediatric patients with inflammatory bowel disease with low serum albumin or with no concurrent immunomodulator therapy 32 . In retrospect, it can be concluded that the adult weight‐based dosing was not appropriate for the pediatric label 32 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, only patients with IBD had detectable ADAs in our cohort, begging the question whether the real-world dosing practices observed in our IBD cohort (median [IQR] of 7.7 [6.2,9.4] mg/kg every 6 [4,8] weeks) are adequate to prevent loss of treatment response to IFX. Two other recent analyses have similarly questioned the adequacy of standard 5 mg/kg IFX dosing every 8 weeks for pediatric IBD, advocating for treat-to-target approaches for IFX [25,26]. No patients with uveitis or JIA had ADAs or trough levels < 5 μg/mL, however, unlike IBD, there are no established IFX therapeutic trough targets currently utilized for JIA or uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…For adalimumab, the approved induction regimen in PIBD ranges from 40 mg at week 0 and 20 mg at week 2 to 160 mg at week 0 and 80 mg at week 2 based on the weight of the patient, and disease severity assessed by a physician. Maintenance therapy with adalimumab is administered biweekly but may be enhanced to weekly therapy and/or by doubling the maintenance dose [8,9]. Infliximab and its biosimilars are licensed for use in children who are at least six years of age and have moderate to severe Crohn's disease or ulcerative colitis, and adalimumab only recently for such patients with ulcerative colitis in addition to Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%